Large-scale meta-analysis and precision functional assays identify FANCM regions in which PTVs confer different risks for ER-negative and triple-negative breast cancer - Billaud, Amandine; Figlioli, Gisella; Mooser, Clémence; Casamassima, Irene; Azzoni, Violette; Srivatsa, Jahnavi; Colombo, Mara; Caleca, Laura; Ahearn, Thomas U.; Andrulis, Irene L.; Antoniou, Antonis C.; Beckmann, Matthias; et al. (The Breast, 2026)
The breast cancer risk conferred by germline protein truncating variants (PTVs) in known and putative breast cancer genes has been extensively investigated. However, the effect of FANCM PTVs on breast cancer risk remains unclear. Our previous clinical, genetic and functional results on the N-terminal p.Arg658∗ and the two C-terminal p.Gln1701∗ and p.Gly1906Alafs∗12 variants suggested that FANCM PTVs may confer different risks for ER-negative (ER-neg) and triple-negative (TN) breast cancer subtypes. Here, we performed meta-analyses of seven studies totaling 144 681 breast cancer cases and 123 632 controls. FANCM PTVs were tested for association with breast cancer risk overall and the disease clinical subtypes by single variant and burden analyses. Two CRISPR-Cas9-based functional assays were also conducted to test the fitness of cells after knock-in of the p.Arg658∗, p.Gln1701∗ and p.Gly1906Alafs∗12 PTVs and the sensitivity of different FANCM regions to genome editing. Our results suggest that the N-terminal FANCM region upstream of p.Tyr725 harbors essential functions, whereas downstream regions appear dispensable. This is supported by our genetic data which indicate that all FANCM PTVs, excluding the two C-terminal p.Gln1701∗ and p.Gly1906Alafs∗12, are associated with an increased risk of ER-neg (OR = 1.41, P = 0.023) and TN (OR = 1.64, P = 0.0023). Notably, PTVs upstream of AA position 670 are associated with a moderate risk of developing TN breast cancer, and that even when the p.Arg658∗ carriers were excluded from the analysis. Importantly, our results confirm previous data indicating that p.Arg658∗ carriers are at moderate risk of developing ER-neg (OR = 2.08, P = 0.030) and TN (OR = 3.26; P = 0.0034), whereas carriers of p.Gln1701∗ and p.Gly1906Alafs∗12 should not be considered at increased risk. Our data are useful for counseling carriers of FANCM PTVs, but further analyses are warranted to obtain more precise risk estimates.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Breast cancer risk; CRISPR-Cas9; FANCM; Gene editing; Genetic predisposition; Meta-analysis